Investigating the role of non-pharmaceutical interventions (NPI) during pandemics: COVID-19 as an example - Elaheh Abiri; Rasoul Raesi; Maryam Haji Ghasem Kashani (BMC Research Notes)
Abstract Background and objective The coronavirus pandemic, with a wide range of clinical manifestations, is considered a serious emergency in increasing anxiety for vulnerable groups of young people such as students. The purpose of this study is to look into how COVID-19 affects depression and anxiety in students at Damghan University. It also aims to determine how non-pharmaceutical intervention (NPI) education affects COVID-19 anxiety and related aspects. Methods This is a descriptive-analytical cross-sectional study conducted on 276 students from Northeast Iran in 2022 using the convenience sampling method. The data were collected by posting the standard electronic questionnaire of the Coronavirus Anxiety Scale (CAS) on the study site’s popular social media platforms. Participants were also given online access to the data collection (NPI) training protocols. Data were analyzed using SPSS-22 statistical software and descriptive and inferential statistical tests. Results 42.3% of participants in the study did not use or used very little of the Infection Prevention and Control (NPI) education, and considering participants’ concerns about contracting COVID-19, 7.97% were somewhat concerned, while 58.3% were considered highly concerned. This result indicates that not using (NPI) education leads to increased anxiety. Most participants reported being highly compliant with using NPI trainings and COVID-19 prevention guidelines (57.6%), and 68.4% believed that COVID-19 will soon be eradicated. This result shows that (NPI) education lead to increased hope and decreased anxiety. Conclusion In the near future, these findings may be helpful in the creation and execution of preventative initiatives and coping mechanisms.